Antiretroviral Treatment Adherence: Knowledge and Experiences among Adolescents and Young Adults in Soweto, South Africa - Stefanie Hornschuh; Janan Janine Dietrich; Celokuhle Tshabalala; Fatima Laher (AIDS Research and Treatment)
Human immunodeficiency virus (HIV) management of adolescents and young adults (AYAs) is particularly pertinent to sub-Saharan Africa, where the pediatric HIV burden is marked. Antiretroviral treatment (ART) adherence is a major challenge for AYAs. This qualitative study explored knowledge and experiences of adherence amongst AYAs attending treatment at the Perinatal HIV Research Unit (PHRU), Soweto, South Africa. Four focus group discussions (FGDs) and eight in-depth interviews (IDIs) were conducted with HIV-infected 15–25-year-old ART recipients. Transcripts were coded thematically. Participants (n=26) were aged median 18.5 years, 59.1% female and 69.2% virally suppressed <400 cp/ml. Three main themes emerged during FGDs and IDIs: (i) correct knowledge about how to be adherent, benefits, and nonadherence consequences, (ii) social, personal, and medication-related barriers to adherence, and (iii) reminder, concealment, and motivational strategies to optimize adherence. Interventions to improve AYA adherence could focus on practical strategies, including status disclosure and medication concealment.